Twenty years later: the new perspectives of the Palermo Convention (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
This essay illustrates the modernity and prospects of the United Nations Convention against Transnational Organized Crime twenty years after its adoption. The author focuses on the potential contribution that the so-called "Falcone Resolution" could bring to the strengthening of international cooperation in the field of preventive measures on assets, judicial cooperation, and transnational investigations, in particular thanks to new tools such as joint investigative bodies, liaison magistrates and the use of special investigative techniques.
Keywords: United Convention against Transnational Organized Crime; Falcone Resolution; international investigative and judicial cooperation; asset prevention measures